THE ROLE OF FUTURES AND OPTIONS IN HEDGING CURRENCY RISKS - Bakoeva Gulbakhor (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
This paper examines the role of futures and options in managing and hedging currency risk in international financial markets. Currency risk, also known as exchange rate risk, arises from fluctuations in foreign exchange rates that affect international trade, investment, and corporate earnings. The article explores the mechanisms of currency futures and options, evaluates their effectiveness as hedging tools, and presents empirical evidence from global corporations and emerging market economies. It also discusses challenges such as basis risk, transaction costs, and market volatility.